2016
DOI: 10.1590/0103-8478cr20151500
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and productive significance of ovine toxoplasmosis in Southern Brazil

Abstract: This research aimed to determine incidence of Toxoplama gondii infection in Corriedale sheep in southern Brazil during pregnancy and the extent of associated losses. Blood samples were collected from 411 Corriedale sheep in two flocks at different locations in the state of Rio Grande do Sul (Brazil). Presence of T. gondii was diagnosed by the Indirect Fluorescent Antibody Technique (IFAT RESUMO Este trabalho tem como objetivo determinar a incidência da infecção pelo T. gondii em ovinos, durante o período gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Between August and October 2016, a cross-sectional study was carried out in 319 randomly selected sheep, females and males, from one to 11 years old, from 14 rural properties in Northwestern Rio Grande do Sul State, Brazil (Table 1). The software EpiInfo 7.1.5 [5] was used to determine the minimum number (n) of samples required using 20.2% as expected prevalence [24], a margin of error of 5%, 95% confidence interval and using the total population of 327,828 sheep in the studied region, according to data from the Brazilian Institute of Geography and Statistics [18].…”
Section: Animal Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Between August and October 2016, a cross-sectional study was carried out in 319 randomly selected sheep, females and males, from one to 11 years old, from 14 rural properties in Northwestern Rio Grande do Sul State, Brazil (Table 1). The software EpiInfo 7.1.5 [5] was used to determine the minimum number (n) of samples required using 20.2% as expected prevalence [24], a margin of error of 5%, 95% confidence interval and using the total population of 327,828 sheep in the studied region, according to data from the Brazilian Institute of Geography and Statistics [18].…”
Section: Animal Samplingmentioning
confidence: 99%
“…Rio Grande do Sul state is the biggest producer of sheep in Brazil [18] and these animals are used for the production of meat, milk and genetic material. A research on the occurrence of the disease in sheep from another mesoregion of this state suggested a production decrease equivalent to 1.87% per year, with decreased number of lambs per ewe [24]. These numbers warn on the necessity to monitor the infection and to find means to improve production efficiency [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in different areas of the world have shown that T. gondii could appear as a life-threatening zoonotic parasite of fetuses of sheep, causing considerable economic losses ( 1 ). For example, the costs of congenital human toxoplasmosis in the UK and annual loss for ovine toxoplasmosis in Brazil have been estimated at $1.2–12 and $1.491 million respectively ( 5 , 6 ). The prevalence rate of toxoplasmosis in aborted fetuses in different areas of the World have been reported to be 23.1% in Spain, 18.1 % in Italy, 17.5% in the USA, and 10.6% in Germany ( 7 – 10 ).…”
Section: Introductionmentioning
confidence: 99%